Histology of Callogenesis in Diploid Bananas (Musa acuminata, AA Group) Kluai Sa and Kluai Leb Mu Nang - Kamnoon KANCHANAPOOM; Korn KORAPATCHAIKUL (Notulae Scientia Biologicae, 2012)
Yellow compact calluses were induced from in vitro-grown shoot tips of diploid bananas (Musa acuminata, AA group) Kluai Sa and Kluai Leb Mu Nang on a modified Murashige and Skoog (MS) medium containing 100 mg/L malt extract, 50 mg/L proline, 50 mg/L cysteine, 100 mg/L glutamine, 1 mg/L biotin, 7 mg/L Dicamba and 2 mg/L TDZ. Green shoot buds were induced after transfer of the yellow compact calluses to the same MS medium but supplemented with 1 mg/L NAA and 3 mg/L BA and plant regeneration was achieved through organogenesis in callus cultures. Regenerated shoots were rooted on MS medium containing 0.2% activated charcoal but without plant growth regulators. Histological analysis revealed that calluses originated from small dense cells with well stained cytoplasm and nucleus typical of meristematic cells.